KAJIAN PERSEBARAN RUANG TERBUKA HIJAU DI KECAMATAN MALALAYANG KOTA MANADO - Rumagit, Michelle Valerie; Luntungan, Jooudie N.; Pioh, Diane D. (Soil and Environment Journal, 2021)
STUDY OF GREEN OPEN SPACE DISTRIBUTION ON MALALAYANG DISTRICT MANADO CITY This research is intended to know if the distribution and availability of GOS in Manado City are corresponding to the spatial plans. The method used in this research is descriptive comparative. The data on the distribution of green open space was obtained through a comparison of the Manado City Land Use Map which was readjusted on Worldview 2 (2015) satellite imagery with the Manado City Spatial Plan Map, especially in Malalayang District based on the classification of green open space types. While the data on the availability of green open space is obtained from the comparison of the total area of the existing green open space in the district of Malalayang. The results showed that the existing green open space in Malalayang District was 123.80 ha. However, the existing green open space area still has to be added to an area of 342.91 ha because it has not met the planned target. Based on the population, the availability of RTH Taman Kelurahan in Malalayang sub-district has been met with an area of 5.05 m²/capita, while the availability of RTH for burial areas has not been met with an existing area of 0.4 m²/capita while what should be available is 1.2 m²/capita.